Immunogenicity of anti-TNF-α biotherapies. I. Individualized medicine based on immunopharmacological evidence - Bendtzen, Klaus (Frontiers in Immunology, 2015)
Specific inhibition of the cytokine, tumor necrosis factor-α (TNF), has revolutionized the treatment of patients with several autoimmune diseases, and genetically engineered anti-TNF antibody constructs now constitute a heavy medicinal expenditure. All currently used anti-TNF biopharmaceuticals may lower disease activity and, in some patients, induce remission. Unfortunately, not all patients respond adequately, and safety may be compromised by immunogenicity with the induction of anti-drug-antibodies (ADA). Assessment of drug pharmacokinetics and ADA is increasingly recognized as a requirement for safe and rational use of biopharmaceuticals. In addition, testing-based strategies rather than empirical dose-escalation may provide more cost-effective use of TNF-antagonists as this allows individualized patient-tailored strategies rather than the current universal approach to anti-TNF biotherapies. The objective of the present minireview - and the accompanying article - is to discuss the reasons for recommending assessments of circulating drug- and ADA levels in patients treated with anti-TNF biopharmaceuticals and to highlight some of the methodological issues that obscure cost-effective and safer ways of using these therapies.